ChemInform Abstract: Cobalt(III)‐Catalyzed Allylation with Allyl Acetates by C—H/C—O Cleavage. Issue 45 (November 2015) - Moselage, Marc; Sauermann, Nicolas; Koeller, Julian; Liu, Weiping; Gelman, Dmitri; Ackermann, Lutz
Abstract Reaction proceeds regioselectively at the less hindered ortho‐position next to the directing group.